PENGARUH MANAJEMEN MODAL KERJA, UMUR PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Isa Agid Wibisana; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe objective of this research is and analyze of Working Capital Management, Firm age, Firm size On Profitability in the manufacture company that is listed at the Indonesian Stock Exchange in period 2015 – 2017. Data analysis that is used in this research is double linier regression. This research take manufacture company that is listed at The Indonesian Stock Exchange in period 2015 – 2017 as population of this research, purposive sampling metode become data collecting technique. The result of this research showed that cash conversion circle (CCC) influence negative significantly on Profitability (ROA), it is proven by t statistic = -2,692 (0,008 < 0,05). Partially, firm age has significant positive influence on Profitability (ROA), it is Proven by t statistic = 2,292 (0,023 < 0,005). Meanwhile, Firm Size affect on Profitability (ROA) positive significantly, it is proven by t statistic = 4,201 (0,000 < 0,05).